PERANCANGAN SISTEM PRESENSI PADA PT SUCOFINDO CABANG MAKASSAR MENGGUNAKAN METODE WATERFALL - Hardiani, Tikaridha; Indah, Mahrunisa (Information System Journal, 2024)
Presence is a very important thing to do for some people who carry out active activities as proof of supporting attendance and can usually be used as a salary calculation that has been agreed upon by the contract of both parties. PT Sucofindo is one of the companies under the auspices of BUMN which accepts apprentices in various positions according to the company's needs. One need that has not been properly met is the use of automatic presence for apprentices at PT Sucofindo Makassar branch. Presences are still carried out manually using books, which are vulnerable to damage and counterfeiting. The use of a system for attendance is very necessary so that intern employee data is safer from damage and there is no falsification of attendance. The method used is the waterfall method which is carried out up to the interface design